Citation practices of postgraduate students writing literature reviews (UCL Press, 2018)
Writing a literature review requires highly sophisticated academic literacies. Many postgraduate students find this genre a challenge. While there is a growing awareness of the need for explicit pedagogy to support students writing this genre, many pedagogical interventions fail to move beyond a focus on citations as a stylistic convention or as a way of avoiding plagiarism. What is missing is a pedagogy that relates citing to the more complex, fluid conceptual and ontological practices that are implicit in academic contexts. The purpose of this paper is to explore the citation patterns, complexity and discursive practices in master's students' literature reviews, and to inform pedagogy.